A Method Of Rolling Steel Or Iron Eye-Bars - Charles Macdonald (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1879)
WROUGHT-IRON eye-bars for bridges and roofs, designed upon what is known as the pin connection system, have been successfully manufactured in this country for some years. The most approved methods employed have been the hydraulic upsetting process, and by die-forging under a hammer. In upset eyes the fibre of the iron is necessarily much distorted ; and in bars of considerable size, this disturbance seriously impairs the strength of the connection. Mr. Collingwood, in discussing my paper on "Proportions of the Heads of Eye-bars," read before the American Society of Civil Engineers, Jan. 21st, 1874, submitted sketches of certain bars intended for the anchorage of the East River bridge, which had been exposed to the action of sulphuric acid a sufficient length of time to thoroughly cleanse the surfaces, and expose the condition of the fibre. These sketches are here reproduced for the purpose of illustrating the effect of this methpd of manufacture. In Figs. 1, 2, and 3, it will be observed that the fibres at A, and E, have been folded back upon themselves and otherwise twisted and disturbed, in a manner not calculated to inspire confidence in the integrity of the connection. To compensate for this defect, a large excess of metal is thrown into the eye; but a method of manufacture which involves such a necessity, even although it be the one giving the best results thus far, all things being considered, is far from being perfect.